Remembering the students’ learning as a reference for teacher reflection: the case of the education degree at the University of Murcia (2005–2010) - Torres Soto, Ana; Vallejo Ruiz, Mónica; Martínez Valcárcel, Nicolás (Profesorado, Revista de Currículum y Formación del Profesorado, 2012)
The students’ perspective has taken center stage in the research activities of recent years. Following this methodology, this paper presents some results of the memories of student learning in Education in the University of Murcia and the link between these results and what teachers in planning programs for their classes. From this analysis we can highlight, the one hand, the preeminence of memories related to theoretical content to the detriment of practical activities, on the other hand, the close relationship between the content recorded by the students and planned by the teachers, and finally, the significance that have led to some practical activities for students. From these findings, this paper is a thoughtful contribution for those teachers who conceived entry into the European Higher Education Area as an opportunity to discuss and rethink their own educational practice, considering that one of the basic principles that underpin this reform is the renewal methodology as one of the pillars to get a competency-based learning model. Finally, it presents some future research will try to provide some answers to the uncertainty created following the introduction of new degrees and new educational approach based on the acquisition of skills: Has there been a methodological change real? Is it still working through the distinction between theoretical and practical?